(untitled) (The Lumbini Journal of Business and Economics, 2022)
Post the outbreak of COVID different studies have been conducted to find the impact of it on various aspects such as physical and mental state of human lives, business, industries, economy, and so on. With the objective of assessing the effect of COVID-19 on Nepalese stock market (NEPSE), using NEPSE index and market turnover as independent variable and taking 1st 6 months’ every operating day data since active COVID cases were seen, this paper tests two hypotheses. First the median of active COVID cases is found, considering as the good mid position indicator, then the cases above the median point are divided as High COVID case situation and Low COVID situation. The non-parametric test Mann-Whitney U-test is applied that finds: 1st: the NEPSE index was increasing during the high COVID cases than that of low COVID situation and 2nd: NEPSE market turnover was also increasing during the high COVID cases than that of low COVID situation. This concludes with significant positive effect of COVID on Nepalese stock market. Digitization of NEPSE, leisure time with people, their sentiment to enter the stock market when stock prices are low and optimism that prices of stock would increase in the future, are some of the factors contributing to the increase in NEPSE performance during high COVID situation.